Cost benefits of UK hospital pharmacy interventions: unlicensed medicines dispensed in the community. Issue 2 (12th March 2012) - Terry, D.; Sinclair, A.; Patel, I.; Wilson, K.
Abstract : Background: Birmingham Children's Hospital (BCH) issues over 36, 000 prescriptions each year that are dispensed by community pharmacists at a cost exceeding £2.2 million. Costs are incurred by the NHS and are rising. Some of these prescriptions include unlicensed medicines (ULMs). At present pricing of ULMs is unregulated in the UK. Purpose: To identify drug-related cost benefits of hospital pharmacy interventions for ULMs prescribed by hospital physicians but dispensed in the community. Materials and methods: Clinical pharmacists reviewed and, if necessary, modified hospital physician-prescribed out-patient prescriptions prior to being dispensed by community pharmacists (the intervention). Preintervention drug costs (net ingredient costs and dispensing fees) were estimated using historical data held on ePACT database and were compared with intervention drug costs identified through payment systems. Results: During the period 8 April to 30 September 2011, 442 prescriptions (638 items) were reviewed. These included 81 items (13%) for ULMs. Interventions on ULMs included: 17 (21%) drug or dose changes; 50 (62%) quantity changes and 51 (63%) where the prescription was re-directed to be dispensed under hospital control (either by a community pharmacy partner hired by BCH, or by the BCH Pharmacy itself). Drug-related cost benefits of the interventions are estimated to exceed £70, 000. Conclusions: This study identifies drug-related financial benefits of hospital pharmacist interventions when ULMs are prescribed by hospital physicians for children at home and dispensed by community pharmacists. This finding supports proposed innovations in NHS processes, that providing long-term medicines for children at home should be led by secondary care.